Measuring the Role of ROA in Boosting Profit Distribution Management (PDM) Sharia Commercial Banks (BUS) - Ardiani Ika Sulistyawati; Saifudin Saifudin; Aprih Santoso; M. Hasan Ma'ruf (Jurnal Ilmiah Ekonomi Islam, 2021)
This study aims to analyze the effect of BOPO and CAR on Profit Distribution Management (PDM) with ROA as a mediating variable in Sharia Commercial Banks (BUS). This study uses the object of all Sharia Commercial Banks (BUS) registered with Bank Indonesia for the period 2015 - 2019. The sampling method used in this study is the census method so that all populations are simultaneously sampled. The analytical tool used to test the hypotheses proposed in this study is to use path analysis where there are two independent variables, one mediating variable and one dependent variable. The results showed that: 1) BOPO partially had no effect on ROA. 2) CAR partially has a positive and significant effect on ROA. 3) BOPO partially has a negative effect on PDM. 4) CAR partially has a positive and significant effect on PDM. 5) ROA partially positive and significant effect on PDM. 6) ROA does not mediate the effect of BOPO and CAR on PDM. Keywords: BOPO, CAR, ROA, PDM